The development of knowledge sharing culture in construction industry - Low, Lisa Seow Wei; Mohammed, Abdul Hakim (Faculty of the Built Environment, University of Malaya, Kuala Lumpur, Malaysia, 2005)
This research seeks to shed light on the factors that stimulate the development of organization knowledge sharing culture. The issue of intention to knowledge management is as important as having positive attitudes and commitment towards effective knowledge sharing culture. This is because right organization characteristics along with right work practices conducive to knowledge sharing influence the employees’ behavior. The objectives of this study are to: (a) identify the factors that promote the development of knowledge sharing culture, (b) identify the best practices for each factor that promotes the development of knowledge sharing culture, and (c) investigate the degree of relationship between the factors and the development of knowledge sharing culture. For the purpose of this study, Sarawak construction firms will be taken as respondents. The companies selected must have experienced in handling of a construction contract with value of RM1 million. The study will be carried out by using two major approaches that are questionnaire survey and case studies. Descriptive analysis and one-sample t test will be applied to analyze the factors and their significant relationship in promoting knowledge sharing culture. The final product of this study is composed of strategies, guidelines and tools for effective knowledge sharing practice within organization.